Effect analysis on strategy implementation drivers - Sorooshian, Shahryar; Zulkifli, Norzima; Ismail, Mohd Yusof; Mohd Yusuff, Rosnah (IDOSI Publications, 2010)
Currently, the strategy implementation is believed to be a dynamic activity within strategic management process. The main objective of this research is to examine the structural relationships between strategy implementation and performance within the small and medium manufacturing firms. In order to implement strategy effectively, it is crucial to consider several organizational issues. The literature indicates that, several researchers have identified three fundamental factors in Strategy Implementation: the structure, leadership style and resources. The current research particularly discusses the main drivers of strategy implementation, prevailing in the smaller industries. In this regard, empirical relationships are established relating strategy implementation and performance of the firm. We provide a structural equation model on the relationship among drivers of strategy implementation and organization performance and also sensitivity analysis on the drivers.